2016
DOI: 10.1186/s13065-016-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic glycosides isolated from Pogostemon cablin (Blanco) Benth. as novel influenza neuraminidase inhibitors

Abstract: BackgroundInfluenza is historically an ancient disease that causes annual epidemics and, at irregular intervals, pandemics. At present, the first-line drugs (oseltamivir and zanamivir) don’t seem to be optimistic due to the spontaneously arising and spreading of oseltamivir resistance among influenza virus. Pogostemon cablin (Blanco) Benth. (P. cablin) is an important traditional Chinese medicine herb that has been widely used for treatment on common cold, nausea and fever. In our previous study, we have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“… 16 The first step in the search for novel potential drugs is often a simple screening of some promising sources, such as traditional medicinal plants. 17 , 18 The identified compounds that often possess only limited neuraminidase-blocking activity can be further used as base molecules for design of novel potent inhibitors. 19 , 20 However, the occurrence of naturally present neuraminidase inhibitors is not limited to plants.…”
Section: Introductionmentioning
confidence: 99%
“… 16 The first step in the search for novel potential drugs is often a simple screening of some promising sources, such as traditional medicinal plants. 17 , 18 The identified compounds that often possess only limited neuraminidase-blocking activity can be further used as base molecules for design of novel potent inhibitors. 19 , 20 However, the occurrence of naturally present neuraminidase inhibitors is not limited to plants.…”
Section: Introductionmentioning
confidence: 99%
“…P. cablin, S. baicalensis and A. capillaris in the Ganlu Xiaodu Decoction are widely used herbal medicines for their antiviral effects. 30 , 31 , 32 S. baicalensis is commonly used for upper respiratory tract infections and in particular for its anti-influenza viral activities in H1N1 and H3N2 infections. Moreover, the derivative S. barbata D. Don inhibits the main proteases of SARS-CoV-2 infection (Mpro and TMPRSS2) and replication protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wu et al reported that patchouli downregulates the expression of inflammatory cytokines such as interferon-γ (IFN-γ) and interleukin-4 (IL4) (30). According to Liu et al, polyphenolic compounds isolated from patchouli may have potential as novel anti-influenza agents due to their neuraminidase inhibitory activity (31). Radix scutellariae, another component of the QXQJ oral solution, has been confirmed to protect influenza A virusinfected mice by inhibiting neuraminidase activities and remarkably decreasing lung virus titers (32).…”
Section: Discussionmentioning
confidence: 99%